Analisis Prinsip Non Intervensi Hukum Internasional Dalam Konteks Perang Teluk 1 Antara Irak-Iran - Nuralisa, Rusaila; Hotima, Desi Patul; Ukas, Ukas (Prosiding, 2024)
The Iran-Iraq War (1980–1988) began with a territorial conflict linked to the Shatt al-Arab River and Khuzestan territory. The 1979 Islamic Revolution in Iran also led to political changes in the Middle East. Provocations and interference from other countries with military aid, economic embargoes, and legal and political interventions make the conflict, increasingly uncertain and or worsening. To look at the principle of non-intervention in the context of the Iran-Iraq war. The research uses a qualitative approach, examining secondary literature and international legal documents. The outcome of this discussion covers any principle of intervention in international law, any exception to the non-intervention principle, how intervention affects both conflicting states. On the basis of its national interests, the presence of the United States has changed and participated in changing political and military behavior in the Middle East.